Targeting the formation of estrogens for treatment of hormone dependent diseases–current status - Rižner, Tea Lanišnik; Romano, Andrea (Frontiers in Pharmacology, 2023)
Local formation and action of estrogens have crucial roles in hormone dependent cancers and benign diseases like endometriosis. Drugs that are currently used for the treatment of these diseases act at the receptor (i.e., they interfere with the hormone receptor) and at the pre-receptor levels, targeting the local formation of estrogens. Since 1980s the local formation of estrogens has been targeted by inhibitors of aromatase that catalyses their formation from androgens. Steroidal and non-steroidal inhibitors have successfully been used for treatment of postmenopausal breast cancer and have also been evaluated in clinical studies in patients with endometrial, ovarian cancers and endometriosis. In the last decade also inhibitors of sulfatase that catalyses the hydrolysis of inactive estrogen-sulfates entered clinical trials for treatment of breast, endometrial cancers and endometriosis, with clinical effects seen in breast cancer especially. More recently, inhibitors of 17beta-hydroxysteroid dehydrogenase 1, an enzyme responsible for formation of the most potent estrogen, estradiol, have shown promising results in preclinical studies and have already entered clinical evaluation for endometriosis. This review aims to overview the current status on the use of hormonal drugs for the main hormone-dependent diseases. Further, it aims to explain the mechanisms behind the -sometimes- observed weak effects and low therapeutic efficacy of these drugs and the opportunity and the advantages of combined treatments targeting several enzymes in the local estrogen formation, or drugs acting with different therapeutic mechanism.